Taxation Regime as a Factor of Mutually Intergrated Macroeconomic Systems’ Dynamics - Denis Ushakov; Vladimir Bandurin; Alexandr Bandurin (Montenegrin Journal of Economics)
In this article the authors, operating the criteria of rigid and comfortable national taxation regimes, attempt to evaluate the stimulating impact of country’s taxation systems on the dynamics of their macroeconomic growth and country’s participation in the world trade. Based on correlation of indices of tax reformations and trends of the modern countries macroeconomic development, co-authors present their conclusions on the priority importance of the so-called “taxation comfort” in the context of country’s positioning in the global rankings.